Environmental contents in the teaching of chemistry: an analysis in standards, educational books, and assessment matrices in Brazil - Parga Lozano, Diana Lineth [UNESP] (Univ Francisco Jose Caldas, Fac Science & Education, 2017)
Research in sciences education currently complain that is necessary to educate people responsible to act and critical thought about social environmental reality, it requires teachers, curriculum organizations and assessments to work in this perspective. Thus, this research was conducted to determine correspondence between teaching, learning and evaluation of environmental contents in curricula and textbooks for teaching chemistry in Brazil. We did a content analysis of curricular standards in seven chemistry books and in the tests National High School Examination: ENEM. We found that chemistry teaching around environmental contents and teaching strategies in relation to environmental aspects in the curricular parameters and in most of the textbooks analysed are in agreement with the references of the current research in didactics of sciences and environmental education. However, in ENEM evaluation tests there is few content related to the environment, and these few are decontextualized and presented in a traditional way; Therefore, do not meet environmental education policies, which means that there is disarticulation between what is taught according to educational policies and what is evaluated in this national test.
Keywords: pedagogical content knowledge; environmental content; environmental education; teaching chemistry; curriculum materials